Keterlibatan Masyarakat dalam Implementasi Penataan Permukiman Kumuh di Kelurahan Mantuil - Irma Khurniawati; Nasruddin Nasruddin (Lembaga Pengembangan Kinerja Dosen, 2026)
Slum upgrading is a strategic step in improving the quality of life of urban communities, where its success is largely determined by the active involvement of local residents. This study aims to analyze the level of community involvement in the implementation of slum upgrading in Mantuil Village, South Banjarmasin District. Using a descriptive quantitative approach, data were collected through a structured questionnaire from 98 respondents selected using a purposive sampling technique. Data analysis was conducted descriptively to measure the level of participation in four stages of the activity. The results show that community involvement is in the good category, but has an uneven distribution. The highest average scores were found in the utilization stage (30.44) and maintenance stages (30.23), indicating that community participation is driven by the principle of direct benefit from the infrastructure being built. Conversely, participation in the planning and implementation stages tends to be lower due to structural barriers such as time constraints and respondents' economic burdens. These findings confirm that sustainable settlement upgrading requires synergy between community social capital and government policies that are adaptive to the geographic characteristics of the region, particularly related to tidal flooding vulnerability in riverbank areas.